Piezoelectric nanogenerators with high performance against harsh conditions based on tunable N doped 4H-SiC nanowire arrays. (May 2021) - Zhou, Linlin; Yang, Tao; Zhu, Laipan; Li, Weijun; Wang, Shuize; Hou, Xinmei; Mao, Xinping; Wang, Zhong Lin
Abstract: Piezoelectric nanogenerators (PENGs) have been attracting much attention for their high flexibility, low density and outstanding chemical stability in applications of environmental energy harvesting and self-powered sensors. Here, PENGs based on large scale free-standing N doped 4H-SiC nanowire arrays (NWAs) fabricated by anodic oxidation of single-crystalline N doped 4H-SiC wafer are proposed for the first time. Due to N-dopants bring the SiC semiconductors an enhanced piezoelectric performance, the as-prepared PENGs show excellent performance with the peak values of open circuit voltage and short circuit current density of 3.0 V and 200 nA cm −2, respectively. Service stability of PENGs has been proven by 20, 000 consecutive charge-discharge cycles as well. Moreover, the PENGs exhibit high thermal stability against 200 °C and excellent acid-base resistance. The energy generated by PENGs is enough to charge capacitors through a full bridge rectifier without any external power supply, certifying that they can work as standalone nanoscale energy sources. These results innovatively expand the feasibility of 4H-SiC for application in a wide variety of high-performance energy harvesting devices. Graphical Abstract: Piezoelectric nanogenerators based on large-scale freestanding N doped 4H-SiC nanowire arrays with outputs of 3.0 V and 200 nA cm −2 are reported. The as-prepared nanogenerators have a long service life and show good anti-interference ability to frequency. They exhibit high thermal stability against 200 °C and excellent acid-base resistance, and can be widely used in various demanding workplaces. ga1 Highlights: Piezoelectric nanogenerators based on tunable N doped 4H-SiC nanowire arrays are first reported. N doping enhances the piezoelectricity of 4H-SiC. The as-prepared piezoelectric nanogenerators exhibit high thermal stability against 200 ℃ and excellent acid-base resistance.